Information Sales and Strategic Trading - García, Diego; Sangiorgi, Francesco (Review of Financial Studies, 2011)
We study information sales in financial markets with strategic risk-averse traders. The optimal selling mechanism is one of the following two: (i) sell to as many agents as possible very imprecise information; (ii) sell to a small number of agents information as precise as possible. As risk-sharing considerations prevail over the negative effects of competition, the newsletters or rumors associated with (i) dominate the exclusivity contract in (ii). These allocations of information have implications for price informativeness and trading volume, and thus we suggest a direct link between properties of asset prices and financial intermediation. Moreover, as more information is sold when the externality in its valuation is relatively less intense, we find a ranking reversal of the informational content of prices between (a) market structures (market-orders vs. limit-orders); and (b) models of traders' behavior (imperfect vs. perfect competition).